Private Law : Key Encounters with Public Law / [electronic resource] - Barker, Kit; Jensen, Darryn (Cambridge : Cambridge University Press, 2013)
The relationship between private and public law has long been the focus of critical attention, but recent years have seen the growing influence upon private law of statutory intervention, public regulation, corporate globalisation and constitutional and international human rights norms. Such developments increasingly call into question the capacity of private law reasoning to operate in isolation from public institutions and goals. Commencing with three contrasting visions of the nature and importance of distinctions between public and private in the modern day, this book traces a number of encounters between private law and 'public' values in key areas of private law doctrine, such as charity law, commercial law, tort law and class actions, across several jurisdictions. It examines the influence within these fields of public concepts and goals, such as behavioural modification, accountability and anti-discrimination norms, as well as the (reverse) influence that private law has upon ('public') human rights jurisprudence.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Civil law; Public law